Safety and efficacy of fistula closure by endoscopic suturing: a multi-center study - Mukewar, Saurabh; Kumar, Nitin; Catalano, Marc; Thompson, Christopher; Abidi, Wasif; Harmsen, William; Enders, Felicity; Gostout, Christopher (Endoscopy, 2016)
Background and aim: Endoscopic closure of fistulas is desirable but remains a challenge, especially for gastrogastric fistulas. The aim of this study was to assess the success rate for the closure of gastrointestinal fistulas using an endoscopic suturing device.Patients and methods: Electronic records at three medical centers were reviewed to identify patients who underwent sutured fistula closure as recorded on a central database. Demographic details, clinical variables, and details of the endoscopic procedure were recorded.Results: A total of 56 patients (mean age 54 ± 12.7 years) underwent fistula closure. Gastrogastric fistulas were most common (n = 29; 51.8 %). Sixteen patients (28.6 %) had undergone previous failed attempts at closure. Immediate success was universal (n = 56; 100 %). Thirteen patients had persistent closure without any need for further therapies, while 17 underwent additional endoscopic procedures, with successful closure in 4 /17. Only one patient had abdominal pain requiring hospital admission.Conclusion: Sutured closure of fistulas in a single session is safe and can be expected, even in what are known to be challenging cases. Sequential closure for recurrences is sometimes successful in the longer term.